RACIAL DISCRIMINATION TOWARD AFRICAN-AMERICAN IN STEVE MCQUEEN'S 12 YEARS A SLAVE (Universitas Pamulang, 2019)
The movie entitled 12 Years a Slave movie written by John Ridley and directed by Steve McQueen is a movie about the African-American, Solomon Northup, being a slave. This movie is reflection of the real social condition in the era of 1981s such as gets an unequal treatment or discriminative attitudes through the colonizer in United States. The purpose of this study is to uncover the racial discrimination toward the character. As an African- American writer, Ridley depicted a story about an African-American freeman character enslaved in the United States for 12 years. Ridley argues that this condition gives the African- American character to get a position of being mistreated and being segregated in the society. To analyze this novel, the theory of Ali Rattansi (2007) is used to support the concept of the racial discrimination. The result of this study shows that the African-American character in 12 Years a Slave suffers from the racial discrimination trough the mistreated by the superior and also, they are being segregated in society, and finally it leads his existence as the minority.Keyword: African-American, Slavery, Racial Discrimination, Ali Rattansi.